A flow cytometry approach reveals heterogeneity in conventional subsets of murine renal mononuclear phagocytes - Johannes Nordlohne (Nature Portfolio, 2021)
Abstract Mononuclear phagocytes (MNPs) participate in inflammation and repair after kidney injury, reflecting their complex nature. Dissection into refined functional subunits has been challenging and would benefit understanding of renal pathologies. Flow cytometric approaches are limited to classifications of either different MNP subsets or functional state. We sought to combine these two dimensions in one protocol that considers functional heterogeneity in each MNP subset. We identified five distinct renal MNP subsets based on a previously described strategy. In vitro polarization of bone marrow-derived macrophages (BMDM) into M1- and M2-like cells suggested functional distinction of CD86 + MHCII + CD206- and CD206 + cells. Combination of both distinction methods identified CD86 + MHCII + CD206- and CD206 + cells in all five MNP subsets, revealing their heterologous nature. Our approach revealed that MNP composition and their functional segmentation varied between different mouse models of kidney injury and, moreover, was dynamically regulated in a time-dependent manner. CD206 + cells from three analyzed MNP subsets had a higher ex vivo phagocytic capacity than CD86 + MHCII + CD206- counterparts, indicating functional uniqueness of each subset. In conclusion, our novel flow cytometric approach refines insights into renal MNP heterogeneity and therefore could benefit mechanistic understanding of renal pathology.